Islamic Religious Education Learning Management in Shaping Student Character in Schools - Rindi Legista; Syukri Amin; Desi Firmasari; Lety Febriana (Al-Qalam Institue, 2025)
This study explores the role of Islamic Religious Education (PAI) in character formation, particularly in the context of the Independent Curriculum and integrated Islamic schools. The research highlights the importance of religious activities, such as Tadarus (Quran recitation), in fostering a disciplined, focused classroom atmosphere, while also integrating key character values, such as religiosity, discipline, responsibility, honesty, and noble morality, into the curriculum and teaching practices, by using a qualitative case study approach with observation, interviews, and documentation. The findings reveal that while religious practices and value discussions engage students, self-reflection remains moderate, suggesting the need for a more systematic approach to foster deeper personal reflection. The study’s contribution lies in providing a comprehensive framework for managing PAI learning, emphasizing the integration of character education within Islamic schools. Future research should explore the impact of socio-cultural contexts, technology integration, and enhanced self-reflection on character development strategies in PAI education.